IMPLEMENTASI PENCEGAHAN DAN PENANGANAN STUNTING DI KABUPATEN SINJAI - Agus, Agus; Syamsuddin, Syamsuddin; Wahid, Abd; Nawir, Adi (DEMOKRASI, 2025)
The purpose of this study was to determine the implementation of stunting prevention policies in Sinjai Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. This study found that the implementation of Sinjai Regent Regulation Number 40 of 2021 concerning the prevention and handling of stunting in Sinjai Regency has been carried out according to the established indicators. The main difference with previous studies is the focus on data collection related to the implementation of this policy, while previous studies had a different focus. The results of the study indicate that policy implementation can be seen in general from several key indicators. Communication is carried out through socialization and transmission of information to all parties involved, with an explanation of stunting accompanied by props to improve understanding. Clarity of information is important so that the community understands the issue of stunting well. Consistency among all parties involved is needed in implementing activities, supported by adequate resources and active participation from all stakeholders, including health center staff and other parties. Information must be disseminated widely, and the enthusiastic attitude of the implementers plays an important role in accelerating the reduction of stunting. The appointment of bureaucrats is accompanied by cooperation and periodic performance evaluation. The focus on preventing and handling stunting is carried out intensively with a bureaucratic structure that involves all parties as implementers of activities. All parties follow the established Standard Operating Procedure (SOP), and each party is fully responsible for implementation.